PMB PTKIN: Analisis Strategi Branding di Media Sosial Periode 2021-2024 - Khodijah, Nyayu; Apriko, M. Syendi; Trisiah, Anita (Wardah, 2024)
The competition among universities to attract prospective students requires each institution to develop a competitive strategy, i.e., branding strategies, such as those implemented by State Islamic Higher Education Institutions (PTKIN). Each year, the branding strategy for new student admissions at PTKIN differs. This study implements a descriptive qualitative approach to analyze the branding strategies employed by the national committee for PMB PTKIN from 2021 to 2024. The focus of this study encompasses branding elements within the scope of brand design, the effectiveness of communication strategies in terms of supporting facilities and resources, and perceptions involving key stakeholders related to branding. The researchers analyzed the branding strategies utilized during 2021-2024 through observation, document analysis, and unstructured interviews as data complement. The findings indicate that effective branding elements include using relevant narratives, particularly those rooted in religious values, using digital media to target prospective students, and collaborating with Islamic higher education institutions under the Ministry of Religious Affairs. However, the study also identified several challenges, such as the suboptimal use of digital platforms and the gap between the projected brand image and public perception. Based on these findings, this study recommends strengthening the branding strategy by developing a consistent visual identity, increasing digital-based promotional activities, and aligning branding messages with the needs and preferences of the target audience. These findings are expected to assist PTKIN in building a stronger brand to attract prospective students to enroll in state Islamic higher education.